Simulation of gallium nitride vertical fin-shaped field effect transistor for use as thermal neutron detector - Davidson, Bryce L. (Kansas State University, 2024)
Through the use of a radiation detection system simulation framework, a gallium nitride vertical fin-shaped field effect transistor (FinFET) was investigated for output response when utilized as a thermal neutron detector. The FinFET was assumed to have been backfilled between fins with boron carbide, reactive to thermal neutrons. The GaN FinFET response was modeled with radiation transport from MCNP, and semiconductor physics and charge carrier transport using COMSOL Multiphysics. Fabricated FinFET devices (not neutron reactive) were tested for electrical performance characteristics to aid in the tuning of the COMSOL FinFET model. Through time-dependent simulation studies, the drain current response pulse to a single event was collected. This was done for several input parameters including particle type, energy, location of entry, and angle of entry to produce a data look-up table. By integrating the current pulses over time, the induced charge was calculated. Using the results of the radiation transport PTRAC file in combination with the induced charge database, an integrated charge spectrum was calculated. Results of this work showed the capabilities of the GaN FinFET for use as a thermal neutron detector, through the radiation transport studies, fabricated FinFET device testing, and electronic charge carrier transport studies. The radiation transport studies found a thermal neutron detection efficiency of 0.8%. Through the fabricated FinFET device testing, it was found that multifin devices show variation in output characteristics, concluding that tuning and calibrating of detection devices would be necessary. Through the electronic charge carrier transport studies, it was found that simulated ionization could be detected through the drain current, where holes contributed to the most induced charge over time. Overall, the simulated GaN FinFET may detect thermal neutrons inefficiently compared to other sensing technology, but perhaps may be useful with its claimed radiation hardness.
Keywords: Radiation transport; Charge transport; Gallium nitride; Thermal neutron detector; Semiconductor simulation